Implementasi Tenaga Pendidik dalam Meningkatkan Efektivitas Lembaga Pendidikan di MIN 1 Medan - Aisyah Fadilah; Evy Juliani Siregar; Fatimah Azzahra Lubis; Zaidan Kholis; Tengku Darmansah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study analyzes the implementation of teaching staff in improving the effectiveness of educational institutions in MIN 1 Medan. This research uses a qualitative approach, with data obtained through interviews with respondents at MIN 1 Medan. The focus of the research is on the management of teaching staff in an effort to improve the effectiveness of educational institutions. The results show that teaching staff have a crucial role in creating an effective learning environment through improving pedagogical competence, innovation in teaching methods, managing a conducive learning environment, and personal approach to students. This study highlights the important role of educators in achieving educational goals and offers strategies to overcome the challenges.